A multi-valued 350nm CMOS voltage reference - Lourenço, Nuno (2012)
This paper describes, a voltage reference source using sub-threshold MOSFETs. The circuit supports supply voltages ranging from 1.5V to 3.3V and temperature variations ranging from -20ºC to 80ºC. Different values for the voltage reference can be achieved without severe performance impairments. The proposed circuit was produced in the 350nm CMOS process from AMS and occupies less than 0.0335mm2. Simulation and experimental data show that this circuit is able to achieve, a 3mV variation for the entire temperature span and a 2mV variation for the entire supply voltage span.